(untitled) (Journal of the College of Basic Education, 2023)
The study (purposes and provisions related to them) aims to clarify the concept of purposes, by identifying it, and its argument, with an indication of its types and clarifying the types in the Qur’anic verses and the noble hadiths of the Prophet, and then delving into the issue of its paths, with mentioning evidence from the Book, the Sunnah and consensus, and giving examples on it as much as possible.